2010
DOI: 10.4049/jimmunol.0902308
|View full text |Cite
|
Sign up to set email alerts
|

MicroRNA-466l Upregulates IL-10 Expression in TLR-Triggered Macrophages by Antagonizing RNA-Binding Protein Tristetraprolin-Mediated IL-10 mRNA Degradation

Abstract: Material

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

8
177
0
2

Year Published

2012
2012
2021
2021

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 221 publications
(187 citation statements)
references
References 43 publications
8
177
0
2
Order By: Relevance
“…A previous study has also shown that miR-466l enhances the production of immune-suppressive IL-10. 26 Thus, enhancing the expression or activity of miR-466l may be a new approach for both the prevention of virusinduced cytokine storms and the treatment of autoimmune diseases.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…A previous study has also shown that miR-466l enhances the production of immune-suppressive IL-10. 26 Thus, enhancing the expression or activity of miR-466l may be a new approach for both the prevention of virusinduced cytokine storms and the treatment of autoimmune diseases.…”
Section: Discussionmentioning
confidence: 99%
“…A previous report has suggested that miR-466l could bind to the ARE of IL-10 39UTR, thereby upregulating IL-10 expression by antagonizing RNA-binding protein tristetraprolin-mediated IL-10 mRNA degradation. 26 Whether miR-466l can regulate host antiviral innate immune response, specifically type I IFN production, remains unknown. In this study, we focused on the role of miR-466l in this process.…”
Section: Introductionmentioning
confidence: 99%
“…For example, the seed sequence of miR-466l is complementary to the AU-rich element sequence 'AUUUA' of Il-10 mRNA and, thus, can compete with tristetraprolin for the AU-rich element sequence binding, resulting in elevated IL-10 production from macrophages. 107 Thus, it is interesting to identify miRNAs involved in the direct mRNA regulation of TLR-induced cytokine expression.…”
Section: Mirnas In Regulation Of Tlr and Rig-i Pathways Yk LI And Xy mentioning
confidence: 99%
“…In other word, deregulated expression of these miRNAs represents an underlying trigger inducing LN and its pathogenesis (14). Some of these miRNAs directly involve in expression of pro-inflammatory cytokines that dictate magnitude of immune response (15)(16)(17). Within the recent two decades, more than 140 conserved miRNAs were discovered that have specific target site on 72 candidate genes for lupus and LN (18).…”
Section: Discussionmentioning
confidence: 99%